Thermal conductivity of deca-nanometric patterned Si membranes by multiscale simulations. (November 2018) - Zaoui, Hayat; Palla, Pier Luca; Giordano, Stefano; Cleri, Fabrizio; Verdier, Maxime; Lacroix, David; Robillard, Jean-François; Termentzidis, Konstantinos; Martin, Evelyne
Graphical abstract: Abstract: The hollowing of silicon membranes to form a lattice of cylindrical holes, also called phononic crystal, has been used by several experimental groups willing to fabricate efficient thermoelectric modules. The idea is to reduce the thermal conductivity without impacting the electronic conductivity. For several a priori identical materials, i.e. thin films containing periodic cylindrical holes, drastically different levels of thermal conductivity reduction have been reported in the literature: from 1–2 W K −1  m −1 to 15–40 W K −1  m −1, i. e. half the thermal conductivity of the plain membrane. These differences may be due to variations in the geometrical patterns, or to the technological processes specific to each group. It is therefore highly desirable to understand which level of reduction can be expected from the basic concept. In this work, we address the question by applying a fully atomistic framework, the approach-to-equilibrium molecular dynamics (AEMD), to study two deca-nanometric patterns used in the literature and reported respectively with a high and low level of thermal conductivity reduction. For both patterns, the thermal conductivity roughly decreases by a factor 2 only compared to the plain membrane. Thanks to Monte Carlo simulations, in agreement with AEMD for the two patterns, we propose that the origin of stronger reductions could be an increase of the surface roughness during the step of hole fabrication.